Attention bias modification via single-session dot-probe training: Failures to replicate. (December 2015) - Everaert, Jonas; Mogoaşe, Cristina; David, Daniel; Koster, Ernst H.W.
Abstract: Background and objectives: Across three experiments we investigated transfer effects of single-session attention bias modification via dot-probe training. Methods: In experiment 1, participants received training either toward or away from negative images or no-training, and transfer to an affective task-switching task was examined. In two other experiments, participants were trained to orient attention toward either positive or negative words (experiment 2a) or facial expressions (experiment 2b), and transfer to an interpretation bias task was examined. Results: In all experiments, the dot-probe training procedure did not effectively modify biases in attention allocation at the training condition level, but produced a large variability in individual attention bias acquisition within and across conditions. Individual differences in pre-training attention bias and attention bias acquisition were not related to performance on the affective task-switching task or the interpretation tasks. Limitations: The present investigations are limited by the lack of effectiveness of ABM at the condition level, the order in which transfer tasks were administered, and the restricted range of affective symptoms that could moderate training and transfer effects. Conclusions: The findings from three experiments provided no evidence for single-session dot-probe ABM procedures to effectively manipulate attention bias toward negative, away from negative, or toward positive stimuli at a training condition level. At the individual differences level of analysis, again no evidence was found for transfer of attention training. The observations invite further empirical scrutiny into factors that moderate attentional plasticity in response to dot-probe ABM procedures to optimize the conditions for effective implementation and transfer of training. Highlights: Transfer of single-session attention training was examined in three experiments. Dot-probe training procedures did not effectively modify attentional biases. No transfer occurred to non-trained stimuli on an affective task-switching task. No transfer occurred to trained or non-trained stimuli on an interpretation task.